Bentuk dan Jenis Tindak Tutur Bahasa dalam Komunikasi Mahasiswa - Hastuti, Hastuti; Angraini, Nani; Saputra, Adi (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
Forms of speech and types of speech in communication are the objectives of this research. The data collected for this research is speech, because qualitative descriptive methods are used. Research and data collection was carried out using note-taking techniques. Speech acts are the subject of this research because of the forms and types of language speech acts in student communication. In everyday conversation, the form of speech is indicated by the speaker and the conversation partner. The three types of speech in communication are declarative, interrogative, and imperative. On the other hand, students use two types of speech: indirect and direct.